The effect of the NFA rice subsidy program "Tindahan Natin" on the political attitudes of its rural poor household beneficiaries in Barangay Caraudan, Janiuay, Iloilo - Bebelone, Diana Mae Ravidas; Fernandez, Charity Tajos (2009.)
This study described the food security situation in a rural village where an NFA Rice Subsidy Program "Tindahan Natin" is in operation. It analyzes whether or not the Tindahan natin program (IV) affects the political attitudes (DV) of its rural poor household beneficiaries. The research assessed the various levels of external political efficacy, political cynicism, political trust, and cynical statism of thirty three (33) rural poor households (16 non-benificiaries and 17 beneficiaries) in Barangay Caraudan, Janiuay, Iloilo. The study employed the Quasi-Experimental Method, specifically the Nonequivalent Control Group Design (NCGD). Using the non-probability purposive snow ball sampling technique, a survey was conducted which assessed the socio-demographic profile of the respondents and measured their levels of political attitudes through Likert-Scale statements. Results show that the "Tindahan Natin" program by the government has been effective in increasing the accessibility and availability of basic food resources - specifically rice-in Barangay Caraudan. The levels of political trust among the beneficiaries of the food subsidy program is a little bit higher compared to the non beneficiaries, which means that the government program has possibly strengthen the political attitude and outlook towards the government, its institutions and bureaucracy in general. All rural poor households respondents are highly cynical towards the government and the elected leaders and politicians. A substantial majority- regardless of being a beneficiary or a non-beneficiary of the tindahan Natin-are highly dependent on the government's provision of public services addressing food insecurity. There is no difference in the respondents' assessment of the responsive of the government.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2009.
Keywords: NFA Rice subsidy Program -- Janiuay, Iloilo; Tindahan Natin